Psychosocial Stressors at Work and Atrial Fibrillation Incidence: An 18‐Year Prospective Study - Edwige Tiwa Diffo; Mathilde Lavigne‐Robichaud; Alain Milot; Chantal Brisson; Mahée Gilbert‐Ouimet; Michel Vézina; Denis Talbot; Xavier Trudel (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Psychosocial stressors at work, defined by the job strain and effort–reward imbalance at work (ERI) models, were shown to increase coronary heart disease risk. No previous study has examined the adverse effect of psychosocial stressors at work from both models on atrial fibrillation (AF) incidence. The objective of this study was to examine the separate and combined effect of psychosocial stressors at work from the job strain and ERI models on AF incidence in a prospective cohort study. Methods and Results A total of 5926 white‐collar workers (3021 women and 2905 men) free of cardiovascular disease at baseline were followed for an average of 18 years. Job strain (high psychological demands combined with low decision latitude) and ERI were assessed using validated instruments. AF events were identified in medical databases with universal coverage. Hazard ratios (HRs) with 95% CIs were estimated using Cox regression models, controlling for socioeconomic characteristics and lifestyle‐related and clinical risk factors. A total of 186 AF incident events were identified over 18 years. Workers exposed to job strain (HR, 1.83 [95% CI, 1.14–2.92]) and ERI (HR, 1.44 [95% CI, 1.05–1.98]) had a higher risk of AF in fully adjusted models. Combined exposure to job strain and ERI was associated with a 2‐fold AF risk increase (HR, 1.97 [95% CI, 1.26–3.07]). Conclusions Psychosocial stressors at work from the job strain and ERI models are associated with an increased risk of AF, separately and in combination. Workplace prevention strategies targeting these psychosocial stressors at work may be effective to reduce the burden associated with AF.